MAGICAL REALISM DEPICTED IN DISNEY’S FILM ENCHANTED (2007) - Khairunnisa, Aqila (ELite Journal : International Journal of Education, Language and Literature, 2023)
Magical realism is still becoming a theme that is quite attractive to the wider community. This is indicated by the number of film productions that use magical realism as a theme. Disney is one of the companies that quite often produces well-known films that use magical realism for its theme. One of the Disney movies that uses this theme is Enchanted. Enchanted, directed by Kevin Lima and released in 2007, is a film that tells the story of a young maiden named Giselle who lived in an animated magical kingdom named Andalasia. She always wondered that one day she would meet a prince as her true love and live happily ever after with him. However, her wish had to run aground when she was tricked by Queen Narissa who disguised herself as an old woman and caused Giselle to be carried away to the real world, precisely in New York City. There are so many illogical things that happen while Giselle is in the real world, which makes the writer interested in researching this movie using the theory of magical realism from Wendy B. Faris. Faris. The research method that being utilized for this study is descriptive qualitative. The results of this study will be presented with a description of the phenomena that occur and accompanied by several images for proof. The primary data that being used in this study is the Disney’s film Enchanted released in 2007 and directed by Kevin Lima. The results of this study show that Enchanted film has characteristics such as The Irreducible Elements, Phenomenal World, Unsettling Doubts, Merging Realms, and Disruption of Time, Space, and Identity. However, disruption of time is not identified in this movie. This study also discovered how magical realism affects the perspective of the characters in the Enchanted film.